Sharia in power: non-Muslims and the performance of Islamic politics in Aceh public Sphere, Indonesia - Zulkarnaini Zulkarnaini; Muhammad Ansor; Laila Sari Masyhur (Indonesian Journal of Islam and Muslim Societies, 2022)
A structural transformation of the public sphere in contemporary Aceh is marked by the monopoly over religious interpretations by the state and ulema through the enactment of Islamic sharia. This article examines the performance of Aceh’s public sphere with reference to non-Muslim discourses in practising Islamic politics. The data were collected through observations, in-depth interviews, and literature study. Based on the concept of multiple public spheres, this paper argues that the government’s attempts to restrict the performance of public space based on Islamic values and identities is not only unsuccessful but also triggers a counter-public sphere to emerge. The counterpublic sphere has become an arena where its proponents promote their valuable ideas, negotiate identity, or being resistant to in realising aspirations. This study finds out that the visibility of public space is in layers and there may be no connections between one contingent and another, or they even contest. Although they may have similarities in being resistant to dominant narratives, the proponents of public space have many ways, perspectives, or strategies to share their ideas and increase their participation in the more prominent public space.